Comparison of three techniques for genetic estimation of effective population size in a critically endangered parrot. (1st December 2020) - Olah, G.; Stojanovic, D.; Webb, M. H.; Waples, R. S.; Heinsohn, R.
Abstract: Understanding the current population size of small, spatially aggregating populations of species is essential for their conservation. Reliable estimates of the effective population size (Ne ) can be used to provide an early warning for conservation managers of the risks to genetic viability of small populations. Critically endangered, migratory swift parrots Lathamus discolor exist in a single panmictic population in Australia. In their Tasmanian breeding range, they are at severe risk of predation by introduced sugar gliders, exacerbated by deforestation. We used three genetic approaches to estimate Ne using DNA samples genotyped by microsatellite markers and existing life‐history data of swift parrots. Based on all samples, we revealed small contemporary Ne estimates across methods (range: 44–140), supporting the need to urgently address threatening processes. Using the 0.5 Ne /N ratio calculated from demographic data suggests that the minimum potential contemporary population size is below 300 individual swift parrots. This is considerably lower than the published estimates derived from expert elicitation, and accords with modeled estimates of extinction risk in this species. Our study has important implications for other threatened species with unknown population sizes and demonstrates that by utilizing available genetic data, reasonable estimates of Ne can be derived. Abstract : We applied three genetic approaches to estimate effective population size (Ne ) using DNA samples genotyped by microsatellite markers and existing life‐history data of critically endangered swift parrots ( Lathamus discolor ). Our results suggest that the minimum potential contemporary population size is below 300 individuals, which is considerably lower than published estimates derived from expert opinions. Our study has important implications for other threatened species with unknown population sizes and demonstrates that by utilizing available genetic data, reasonable estimates of Ne can be derived.